MISOGYNISTIC IN DIGITAL MEDIA : HATE SPEECH NARRATIVES TOWARDS BEAUTY INFLUENCERS - Santosa, Hedi Pudjo; Ayun, Primada Qurrota; Lukmantoro, Triyono (Interaksi: Jurnal Ilmu Komunikasi, 2022)
Huge numbers of social media users in Indonesia creates a phenomenon of beauty influencers. Selebgram or Instagram celebrities, starts to become a trend when artists wearing veils become a fashion icon for certain groups of communities. The influencers try to expose new identities which were considered old fashioned. However, this beauty influencer phenomenon also initiates hate speech trends. Nature of social media allows people to comment, spread information, and give opinions freely and anonymously, and even create the tendency to write misogynistic narratives. This research is a descriptive textual study using a narrative approach. Narrative in this connection refers to status updates on Instagram, narratives are understood as “small stories” that capture the whole variety of narrative activities that are not represented in the big or canonical narratives. The results of this study indicate that hate speech against female celebrities means that they receive negative judgments and comments from netizens by using religious statements and social norms of society. They provide comments by giving bad labels and giving judgments for their behavior